Isolated Spinal Accessory Nerve Palsy from Volleyball Injury - Holan, Cole A.; Egeland, Brent M.; Henry, Steven L. (Archives of Plastic Surgery, 2022)
Spinal accessory nerve (SAN) palsy is typically a result of posterior triangle surgery and can present with partial or complete paralysis of the trapezius muscle and severe shoulder dysfunction. We share an atypical case of a patient who presented with SAN palsy following an injury sustained playing competitive volleyball. A 19-year-old right hand dominant competitive volleyball player presented with right shoulder weakness, dyskinesia, and pain. She injured the right shoulder during a volleyball game 2 years prior when diving routinely for a ball. On physical examination she had weakness of shoulder shrug and a pronounced shift of the scapula when abducting or forward flexing her shoulder greater than 90 degrees. Manual stabilization of the scapula eliminated this shift, so we performed scapulopexy to stabilize the inferior angle of the scapula. At 6 months postoperative, she had full active range of motion of the shoulder. SAN palsy can occur following what would seem to be a routine volleyball maneuver. This could be due to a combination of muscle hypertrophy from intensive volleyball training and stretch sustained while diving for a ball. Despite delayed presentation and complete atrophy of the trapezius, a satisfactory outcome was achieved with scapulopexy.
Keywords: accessory nerve injuries; cranial nerve XI injury; spinal accessory nerve injury; spinal accessory nerve trauma